2021
DOI: 10.21203/rs.3.rs-296520/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High dose aerosol challenge with Mycobacterium tuberculosis fails to overcome BCG vaccination-induced protection in cynomolgus macaques of Chinese origin: implications of natural resistance for TB vaccine evaluation.

Abstract: This study describes the use of cynomolgus macaques of Chinese origin (CCM) to evaluate the efficacy and immunogenicity of the BCG vaccine against high dose aerosol Mycobacterium tuberculosis challenge. Progressive disease developed in three of the unvaccinated animals within ten weeks of challenge, whereas all six vaccinated animals controlled disease for 26 weeks. Three unvaccinated animals limited disease progression, highlighting the intrinsic ability of this macaque species to control disease in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(86 reference statements)
2
0
0
Order By: Relevance
“…An increase in PPD-specific IFNγ-secreting cells was observed in the animals in group 1 after BCG vaccination, although the response was lower and more short-lived than those observed after BCG vaccination in studies conducted with rhesus macaques [ 23 , 25 , 31 ]. However, the response profiles were similar to those we observed in cynomolgus macaques of Chinese origin, which were able to control a high-dose aerosol challenge of M. tb [ 32 ] and may point to other mechanisms of immune protection afforded by BCG in these cynomolgus macaque populations. Following M. tb infection, an increase in CFP10- and ESAT6-specific IFNγ-producing cells was measured in all animals.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An increase in PPD-specific IFNγ-secreting cells was observed in the animals in group 1 after BCG vaccination, although the response was lower and more short-lived than those observed after BCG vaccination in studies conducted with rhesus macaques [ 23 , 25 , 31 ]. However, the response profiles were similar to those we observed in cynomolgus macaques of Chinese origin, which were able to control a high-dose aerosol challenge of M. tb [ 32 ] and may point to other mechanisms of immune protection afforded by BCG in these cynomolgus macaque populations. Following M. tb infection, an increase in CFP10- and ESAT6-specific IFNγ-producing cells was measured in all animals.…”
Section: Discussionsupporting
confidence: 77%
“…The frequency of responses to these diagnostic antigens is considered to be a biomarker reflective of disease progression, TB disease burden [ 33 ] and antigen load, with high frequencies associated with a poorer postchallenge outcome [ 24 , 25 ]. In the initial period following M. tb challenge and before infection with SIV, ESAT6 and CFP10 responses were lowest in the BCG-vaccinated animals, suggesting that TB disease was more controlled, in line with observations from efficacy assessments of BCG vaccination performed in rhesus [ 24 , 25 ] and cynomolgus macaques of Chinese origin [ 32 ]. The increase in frequency of M. tb-specific IFNγ-secreting cells measured following SIV infection is in line with Diedrich et al, who reported an increase after coinfection with SIV after a latent TB infection [ 11 ], thought to be related to reactivation of TB, reflecting a breakdown in control of TB infection.…”
Section: Discussionsupporting
confidence: 76%